Neurofibrossarcoma associado a neurofibromatose - Silva,Alcino Lázaro da (1998)
The clinical and pathological aspects of neurofibromatosis are summarized and an updated pathogeny of the tumor is made. The malignancy of the NFS senns to be linled to the NF - 1 gene mutations, with loss of the suppressor gene in the chromosone 17 pl. The surgical treatment is always useful because it lowers the pressure and relieves the patient.